1985
DOI: 10.1097/00006254-198506000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Familial Premature Ovarian Failure

Abstract: Premature menopause, ovarian failure younger than 40 years of age, is relatively rare but may preclude childbearing for some women who delay attempts at fertility. We present five kindreds in which a genetic association for premature ovarian failure is strongly suggested. Transmission is either autosomal or (less likely) X-linked dominant in these examples. Chromosomal abnormalities, history of diseases, and toxic chemical or viral exposures previously associated with premature ovarian failure could not be dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
0
39
0
2
Order By: Relevance
“…The incidence of POF is estimated to be 1%. Although some POF cases have been associated with certain genetic factors, the etiology of the majority of POF cases remains unknown (1,11,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of POF is estimated to be 1%. Although some POF cases have been associated with certain genetic factors, the etiology of the majority of POF cases remains unknown (1,11,32).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of genetic and environmental factors have been associated with follicle destruction and early depletion, giving rise to POF (1,18,32). For example, smoking is known to be associated with early menopause, and polycyclic aromatic hydrocarbons, major toxic components of cigarette smoke, cause follicle destruction in experimental animals (31).…”
mentioning
confidence: 99%
“…Familial cases show a clear pattern of dominant inheritance, with expression restricted to females (Mattison et al, 1984). A possible association of the fragile X premutation with premature ovarian failure was first reported by Cronister et al (1991), who found eight women with POF among 61 normal fra(X) heterozygotes.…”
Section: Introductionmentioning
confidence: 99%
“…Although epidemiological evidence based on mother-daughter pairs supports the heritability of menopausal age [95,96] and some Authors reported cases of familial premature menopause [97,98], very little is known about the inheritance pattern of the idiopathic POF. The overall incidence of familial POF ranges between 4% and 31% depending on the inclusion criteria adopted and the availability of a detailed family history [95,96,98].…”
Section: Genetics Of Familial Idiopathic Pofmentioning
confidence: 99%